Exploring Perspectives, Negotiating Computer-mediated Landscapes, and Integrating Technology in Linguistically and Culturally-diverse Learning Spaces - Patricia López-Estrada; Prisca Rodríguez; Maria Bonet (Revista Electronic@ Educare, 2019)
Global trends in the 21st century highlight the importance and necessity of technology use for students to demonstrate their learning processes, thus facilitating their language learning in meaningful technological contexts (Eaton, 2010). This paper seeks to address some issues dealing with the importance of technology in relation to second language learning and teaching, including the benefits, challenges, considerations, and perceptions of teaching with technology. The purpose of this paper is threefold. First, it explores technology in education as it has been commonly construed, challenged, and used. Secondly, it presents technology in education ideas to second language learning, and discusses some benefits and challenges implicit in the interaction of both. Lastly, it shares ways in which the authors, all currently working in diverse educational contexts, have implemented some of the free resources that they collaboratively compiled in an online LiveBinder.